2017
DOI: 10.1186/s12974-017-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

A role for cathepsin Z in neuroinflammation provides mechanistic support for an epigenetic risk factor in multiple sclerosis

Abstract: BackgroundHypomethylation of the cathepsin Z locus has been proposed as an epigenetic risk factor for multiple sclerosis (MS). Cathepsin Z is a unique lysosomal cysteine cathepsin expressed primarily by antigen presenting cells. While cathepsin Z expression has been associated with neuroinflammatory disorders, a role for cathepsin Z in mediating neuroinflammation has not been previously established.MethodsExperimental autoimmune encephalomyelitis (EAE) was induced in both wildtype mice and mice deficient in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 57 publications
0
49
0
Order By: Relevance
“…Furthermore, a comprehensive comparative gene expression analysis of mouse models of multiple sclerosis, AD, and stroke, found that cathepsin X is one of the 18 genes whose expression is increased in all three models of neuroinflammation ( Tseveleki et al, 2010 ). Additionally, Allan et al (2017) showed that mice deficient in cathepsin X have reduced neuroinflammation and dramatically lowered circulating levels of interleukin 1β during experimental autoimmune encephalomyelitis, supporting in vitro studies of novel role of cathepsin X in neuroinflammation ( Pišlar et al, 2017 ). Nevertheless, other experimental models for neurodegenerative diseases, such as for PD, have described the upregulation of the other lysosomal peptidases [reviewed in Pislar and Kos (2014) ].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, a comprehensive comparative gene expression analysis of mouse models of multiple sclerosis, AD, and stroke, found that cathepsin X is one of the 18 genes whose expression is increased in all three models of neuroinflammation ( Tseveleki et al, 2010 ). Additionally, Allan et al (2017) showed that mice deficient in cathepsin X have reduced neuroinflammation and dramatically lowered circulating levels of interleukin 1β during experimental autoimmune encephalomyelitis, supporting in vitro studies of novel role of cathepsin X in neuroinflammation ( Pišlar et al, 2017 ). Nevertheless, other experimental models for neurodegenerative diseases, such as for PD, have described the upregulation of the other lysosomal peptidases [reviewed in Pislar and Kos (2014) ].…”
Section: Discussionmentioning
confidence: 80%
“…*p < 0.05, **p < 0.01, ***p < 0.005, ****p < 0.001, no symbol, not significant. production by macrophages under cholesterol crystals, ATP, MSU, or Alum treatments (Duewell et al, 2010;Oleszycka et al, 2016;Allan et al, 2017). However, these studies didn't explore whether these enzymes are required for NLRP3 inflammasome activation and/or IL-1β secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR‐validated genes related to the central nervous system that were significantly upregulated in domesticated fish were reported to be responsible for the protection of neurons ( camk2b ; Fang, Feng, Zhao, & Liu, 2014), synaptic plasticity ( ctnna2 ; Terracciano et al, 2011), and were found to be involved in counteracting neuroinflammation ( ctsz ; Allan et al, 2017). The genes that were upregulated in eggs from wild broodstock were reported to regulate thalamocortical axon branching ( ntn4 ; Hayano et al, 2014) and are known to be crucial for normal brain development ( gabrb1 ; Halder et al, 2015).…”
Section: Discussionmentioning
confidence: 99%